Evolutionary reconstruction, nomenclature and functional meta-analysis of the Kiwellin protein family - Klemm, Paul; Christ, Marvin; Altegoer, Florian; Freitag, Johannes; Bange, Gert; Lechner, Marcus (Frontiers in Plant Science, 2022)
Crop diseases caused by pathogens critically affect global food security and plant ecology. Pathogens are well adapted to their host plants and have developed sophisticated mechanisms allowing successful colonization. Plants in turn have taken measures to counteract pathogen attacks resulting in an evolutionary arms race. Recent studies provided mechanistic insights into how two plant Kiwellin proteins from Zea mays mitigate the activity of the chorismate mutase Cmu1, a virulence factor secreted by the fungal pathogen Ustilago maydis during maize infection. Formerly identified as human allergens in kiwifruit, the biological function of Kiwellins is apparently linked to plant defense. We combined the analysis of proteome data with structural predictions to obtain a holistic overview of the Kiwellin protein family, that is subdivided into proteins with and without a N-terminal kissper domain. We found that Kiwellins are evolutionarily conserved in various plant species. At median five Kiwellin paralogs are encoded in each plant genome. Structural predictions revealed that Barwin-like proteins and Kiwellins cannot be discriminated purely at the sequence level. Our data shows that Kiwellins emerged in land plants (embryophyta) and are not present in fungi as suggested earlier. They evolved via three major duplication events that lead to clearly distinguishable subfamilies. We introduce a systematic Kiwellin nomenclature based on a detailed evolutionary reconstruction of this protein family. A meta-analysis of publicly available transcriptome data demonstrated that Kiwellins can be differentially regulated upon the interaction of plants with pathogens but also with symbionts. Furthermore, significant differences in Kiwellin expression levels dependent on tissues and cultivars were observed. In summary, our study sheds light on the evolution and regulation of a large protein family and provides a framework for a more detailed understanding of the molecular functions of Kiwellins.